2013
DOI: 10.6061/clinics/2013(01)oa07
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the correlation between dental occlusion and posture using a force platform

Abstract: OBJECTIVES:Force platforms are widely used to evaluate the relationship between posture and dental occlusion. This study evaluated whether force platforms are able to detect eventual postural modifications resulting from dental occlusion.METHOD:A total of 44 healthy volunteers who were given no information on the aim of the study underwent six postural stabilometric exams under different mandibular and visual conditions. Four parameters were considered: sway area, sway velocity, X axis displacement of the cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
42
1
12

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 20 publications
5
42
1
12
Order By: Relevance
“…These data suggest that the postural stability, expressed as CoP path length, maximum CoP speed and confidence ellipse area, is most decreased when the examination was performed in maximum mouth opening condition. assessed 44 healthy volunteers in different conditions (mandibular postural position, mandibular position of centric occlusion and mandibular position with 8-mm thick cotton rolls) and noticed that the position of the centre of the foot pressure was not influenced by occlusal components [5]. The current study showed that there were no differences in the CoP displacement measurement when comparing the mandibular postural position, maximum intercuspation, biting on cotton rolls and maximum mouth opening conditions.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…These data suggest that the postural stability, expressed as CoP path length, maximum CoP speed and confidence ellipse area, is most decreased when the examination was performed in maximum mouth opening condition. assessed 44 healthy volunteers in different conditions (mandibular postural position, mandibular position of centric occlusion and mandibular position with 8-mm thick cotton rolls) and noticed that the position of the centre of the foot pressure was not influenced by occlusal components [5]. The current study showed that there were no differences in the CoP displacement measurement when comparing the mandibular postural position, maximum intercuspation, biting on cotton rolls and maximum mouth opening conditions.…”
Section: Discussionmentioning
confidence: 45%
“…Moreover, changes of different jaws relations also have effect on postural stability [4]. A more recent study (2013) demonstrated a weak correlation between mandibular position and body posture in healthy subjects [5].…”
Section: Introductionmentioning
confidence: 98%
“…The research method then employs a sensible approach that can standardize measurements for comparisons of subjects, and provide measurable guidelines for improving conditions seen in daily practice (Manfredini et al, 2012;Baldini et al, 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…7 Some researchers have examined the relationship between body posture and the mandibular position by using a stabilometer in young subjects, and they concluded that the foot center of pressure is not influenced by asymmetric malocclusion or by different dental positions. [8][9][10] This may indicate a need to focus on the effects of extreme mandibular positions in the elderly population to reveal this relationship.…”
Section: Introductionmentioning
confidence: 94%